PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL INTERVENING - Fivi Anggraini; Yenni Pillisia Seprijon; Siti Rahmi (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2020)
Tight competition between companies in the business world in attracting investors is becoming a strong motivation for them to maximize their firm values. This study aims to determine the effect intellectual capital on firm value with financial distress as an intervening variable on real estate and building construction companies listed in Indonesia Stock Exchange in 2014-2018. Sampling method by using purposive sampling with a total   the samples obtained were 40 from real estate and building construction companies listed in IDX. The data was analysed by using multiple linear regression analysis and path analysis. Data analysis was processed with the SPSS 16. The results of this study showed that intellectual capital have significantly negative effect on financial distress. Simultaneously and partially intellectual capital and financial distress have a significant direct effect on firm value. The indirect test results showed that intellectual capital has a significant effect on firm value with financial distress as an intervening variable.